2019
DOI: 10.1186/s12958-019-0509-4
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovary syndrome and mitochondrial dysfunction

Abstract: Polycystic ovary syndrome (PCOS) is a prevalent hormonal disorder of premenopausal women worldwide and is characterized by reproductive, endocrine, and metabolic abnormalities. The clinical manifestations of PCOS include oligomenorrhea or amenorrhea, hyperandrogenism, ovarian polycystic changes, and infertility. Women with PCOS are at an increased risk of suffering from type 2 diabetes; me\tabolic syndrome; cardiovascular events, such as hypertension, dyslipidemia; gynecological diseases, including infertility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 189 publications
7
119
0
5
Order By: Relevance
“…The change in mtDNA-CN was also uncorrelated with most other clinical variables, including BMI, which was implicated in previous studies [9,42]. Only testosterone appears to be statistically related to the change in mtDNA-CN, signifying that the changes in mtDNA-CN and testosterone were correspondent during treatment with metformin.…”
Section: Discussionsupporting
confidence: 64%
“…The change in mtDNA-CN was also uncorrelated with most other clinical variables, including BMI, which was implicated in previous studies [9,42]. Only testosterone appears to be statistically related to the change in mtDNA-CN, signifying that the changes in mtDNA-CN and testosterone were correspondent during treatment with metformin.…”
Section: Discussionsupporting
confidence: 64%
“…However, the existence of an autonomous mitochondrial epigenetic regulation has been the subject of a long debate over the years with controversial reports stating the presence or absence of mtDNA methylation (Patil et al, 2019). With the improvement of detection techniques, recent studies proposed that similarly to nuclear DNA, mtDNA is also subjected to epigenetic modifications that can influence mitochondrial biogenesis, gene expression and function (Zhang et al, 2019a). A recent study demonstrated non-random patterns of mtDNA methylation, predominantly in a non-CpG context when comparing normal versus liver and breast cancer cells (Patil et al, 2019).…”
Section: Mitochondrial Dna Methylation/demethylationmentioning
confidence: 99%
“…In the reproductive environment, mtDNA copy number can be used as a means of detecting embryo viability . In addition, markers of abnormal mitochondrial metabolism such as ROS, advanced oxidation protein products, catalase, and superox-ide dismutase (SOD) are associated with PCOS (Zhang et al, 2019a).…”
Section: Mitochondria Structure and Functionmentioning
confidence: 99%